Geese, Planks and Sluts: Semantic Derogation of Women in French and Serbian Slang - Đurin, Tatjana Č.; Jovanović, Ivan N. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The paper uses a cognitive linguistic approach to analyse slang lexemes derogatively denoting and qualifying women in two languages neither genealogically close nor in direct contact. Starting from the conceptual metaphor theory and the linguocultural approach, our aim is to determine the similarities and differences related to the cultural knowledge about the concept of women in French and Serbian culture. Our research corpus encompasses examples excerpted from French and Serbian slang and standard dictionaries. The analysis shows that most of the slang expressions that derisively qualify women emphasise physical appearance, intellectual characteristics, and forms of behaviour that the sociolinguistic community assesses as unacceptable and undesirable. The results confirm the deeply rooted and widespread prevalence of collective prejudice, generalisations, stereotypes, and the tendency to marginalise women.